THE IMPORTANCE OF ENSURING INNOVATIVE DEVELOPMENT (Academia Science Repository, 2023)
The article is devoted to the need to develop innovations in the agricultural economy and modern innovative activity of the agro-industrial complex. The prospects for the innovative development of the country's agriculture, which consist in continuous technical, technological and economic renewal of production, are considered.